Hunting paleoceanographic archives of ice sheet-ocean interaction in the northwestern Ross Sea, Antarctica - Kim, Sookwan; De Santis, Laura; Hong, Jong Kuk; Colizza, Ester; Kim, Sunghan; Bergamasco, Andrea; Lee, Sang-Hoon; Kang, Seung-Goo; Lee, Min Kyung; Kim, Hyoungjun; Choi, Yeonjin; Geniram, Andrea; et al. (Frontiers in Earth Science, 2023)
The analysis of sedimentary deposits influenced by bottom currents in glaciated continental margins provide crucial insights into paleo-depositional and oceanographic conditions. These reconstructions enable the assessment of interactions between advance and retreat of grounded ice sheets and past ocean circulation patterns. However, questions regarding these interactions and their specific mechanisms remain largely unanswered due to a lack of data in this remote area. In this study, we conducted a comprehensive analysis by integrating marine geophysical data, surficial sediment cores, oceanographic measurements, and ocean circulation models. Our aim was to understand spatial and temporal variations in sedimentary and oceanographic conditions during the past glacial and interglacial periods in combination with the long-term stratigraphic evolution. By integrating and cross-referencing diverse datasets, we were able to infer how bottom-current-controlled deposits (i.e., contourites) developed along the western bathymetric high of the Central Basin in the northwestern Ross Sea margin, Antarctica. Contouritic deposits lying over and along the flanks of bathymetric highs were identified through their mound-shaped external geometry and acoustically stratified facies, characterized by reflectors pinching toward the moat. Acoustic facies and multi-beam backscatter results, in conjunction with sedimentary core data, revealed contrasting patterns. Bathymetric highs exhibited thin (<10 m thick) coarser-grained sedimentary layers with higher backscatter, while the lower slope and rise displayed thick (>10 m thick), finer-grained stratified sediments with lower backscatter. These findings indicate that seabed winnowing occurred by strong bottom current during past glacial periods as supported by sedimentological analysis. The pathways of the westward-deflected dense shelf water outflow and the westward-flowing along-slope current, 삭제함: Oceanographic and Bathymetric Controls on the Distribution of Contourites 삭제함: